Awareness, behavior and attitudes concerning sun exposure among beachgoers in the northern coast of Peru - Toro-Huamanchumo, Carlos J. (2019)
Background: Skin cancer incidence has increased over the last years, becoming a major public health problem. Objective: To describe the awareness, behavior and attitudes concerning sun exposure among beachgoers in the northern coast of Peru. Methods: We conducted a cross-sectional study in the Pimentel beach, Peru. The "Beach Questionnaire" was used and we surveyed all the beachgoers from 8 a.m. to 4 p.m. and from March 5 to March 19. For the statistical analysis, sun exposure habits, sunburns history, knowledge, attitudes and practices were crossed with sex using the chi2 test. Results: We surveyed 410 beachgoers, the most frequent phototype was type III (40.5%). Only the 13.66% of the respondents correctly answered the seven knowledge questions related to sun exposure and skin cancer. Men more frequently agreed that "when they are tanned their clothes looks nicer" (p = 0.048). Likewise, regarding the questions "Sunbathing is relaxing" and "Sunbathing improves my mood", men agreed or totally agreed with more frequency than women (63.64% vs. 46.15%, p < 0.001; and 61.36% vs 49.15%, p = 0.014, respectively). Regarding sun protection practices, women more frequently used sunshade (p = 0.001) and sunscreen (SPF ≥ 15) (p < 0.001) when compared to the male group. Conclusion: Sun exposure is a potentially preventable risk factor for skin cancer. Thus, awareness of the risks of UVR overexposure and adequate sun-protective behaviors and attitudes are essential. Our results, however, are not as favorable as expected. Public health efforts should encourage sun-safety precautions and intervention campaigns should be carried out in recreational settings, such as the beaches.